SPECIAL CURVES IN THREE DIMENSIONAL FINSLER MANIFOLD F3 - Ergut, Mahmut; Kulahci, Mihriban (Inst Applied Mathematics, 2014)
In this paper, we study AW(k)-type curves in three dimensional Finsler manifold and we give some characterizations related to these curves.
Keywords: AW(k)-type curves; Frenet formulas; Finsler manifold; Bertrand curves